(untitled) (Bangladesh Journal of Medical Science, 2020)
Objective: Toevaluate the anthelmintic activity of Majoon Sarakhs, a pharmacopoeal Unani formulationonadult earthworm(Eiseniafetida). Methods: Adult earthworms of similar age, size and weight were divided into six groups of 6 each and released in petridishes containing 0.5% CMC in normal saline (control), Albendazole (standard), hydro alcoholic extract (HAEMS), aqueous extract (AEMS), Majoon (MS) and powder (PFMS) of ingredients of MajoonSarakhs in various concentrations (50, 100, 150, 200, 250 and 300 mg/ml). Time for paralysis was noted when no movement was observed. Death was confirmed when the worms neither moved when shaken vigorously nor when dipped in warm water followed by fading away the body colours. Phytochemical analysis and HPLC finger printing were also carried out. Results: All dosage forms of ingredients of MS showed significant anthelmintic (p<0.001) effect in concentration dependent manner when compared to Albendazole. The test formulation paralysed and killed the worms at all concentration, but at higher concentration it took shorter time. The order of activity was HAEMS > AEMS > Albendazole > MS > PFMS at 50mg/ml.At higher dose MS showed better results than Albendazole. Conclusion: on the basis of above results it can be concluded that MS and extracts of its ingredients possess profound anthelmintic activity against tested worms. It validates the claims of Unani physicians that MS is a good anthelmintic agent. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.659-669